The association of type of cannabis product used and frequency of use with problematic cannabis use in a sample of young adult cannabis users. (1st September 2021) - Simpson, Kelsey A.; Cho, Junhan; Barrington-Trimis, Jessica L.
Highlights: Young adult cannabis users demonstrate distinct variations in their expression of cannabis problems. Cannabis product type and frequency of use were consistently associated with classes of problematic cannabis behaviors. Combustible cannabis, vaporized cannabis, and blunts were the strongest predictors of membership in higher risk classes. Further research on types of cannabis products, dosage, potency, and patterns of cannabis problems is needed. Abstract: Research exploring patterns and predictors of problematic cannabis use behaviors among young adults is limited. This knowledge is essential for intervening to prevent abuse and dependence outcomes. Methods: Young adult cannabis users (Mage = 19.2[SD = 0.8]) in Southern California (N = 1007) were classified by patterns of problematic cannabis use from the Cannabis Abuse Screening Test, using Latent Class Analysis. Multinomial regression evaluated the association of frequency of use (no past 30 day use, infrequent [use on 1–2 of past 30 days], semi-frequent [use on 3–9 of the past 30 days], and frequent [use on 10 or more of the past 30 days]) for each cannabis product type (combustible, edible, vaporized, concentrate, blunt) with class membership. Results: Four distinct classes of cannabis-related problems were identified: "non-symptomatic" (no problems; 33.8 %), "non-recreational use" (before noon and when alone; 34.5 %), "moderate use problems" (before noon, alone, and memory problems; 8.0 %), and "severe cannabis problems" (all 6 problems; 23.7 %). Semi-frequent (AOR range: 1.85–4.63;ps<0.05) and frequent (AOR range: 9.18–24.2;ps<0.05) use of combustible and vaporized cannabis, frequent blunt use (AORs range: 4.03–10.3;ps<0.05), and semi-frequent, but not frequent edible use (AOR range: 2.57–2.73;ps<0.05) was associated with higher odds of classification in any problematic use class (vs. non-symptomatic). Conclusions: Differences in cannabis use problems across these classes and their predictors reveal the heterogeneity in cannabis-related problems experienced by young people. Combustible cannabis, vaporized cannabis, and blunt cannabis use may confer the most risk for cannabis abuse and dependency outcomes, with more frequent days of use contributing to increased patterns of risk.